2005
DOI: 10.1016/j.febslet.2005.09.021
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the high sensitivity of muscle fructose 1,6‐bisphosphatase towards AMP

Abstract: Adenosine 5 0 -monophosphate (AMP) inhibits muscle fructose 1,6-bisphosphatase (FBPase) about 44 times stronger than the liver isozyme. The key role in strong AMP binding to muscle isozyme play K20, T177 and Q179. Muscle FBPase which has been mutated towards the liver enzyme (K20E/ T177M/Q179C) is inhibited by AMP about 26 times weaker than the wild-type muscle enzyme, but it binds the fluorescent AMP analogue, 2 0 ,3 0 -O-(2,4,6-trinitrophenyl)adenosine 5 0 -monophosphate (TNP-AMP), similarly to the wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Gizak et al (2008) presented evidence that truncation starting from Pro5 at the N-terminus decreased the sensitivity of muscle FBPase towards AMP. Rakus et al (2005) found that the three-point mutant K20E/T177M/Q179C was inhibited by AMP about 26 times more weakly than the wild-type muscle isozyme. They also constructed two chimeric human FBPases (L50M288 and M50L288; Rakus et al, 2003) in which the N-terminal residues (1-50) were derived from the other isozyme.…”
Section: Discussionmentioning
confidence: 97%
“…Gizak et al (2008) presented evidence that truncation starting from Pro5 at the N-terminus decreased the sensitivity of muscle FBPase towards AMP. Rakus et al (2005) found that the three-point mutant K20E/T177M/Q179C was inhibited by AMP about 26 times more weakly than the wild-type muscle isozyme. They also constructed two chimeric human FBPases (L50M288 and M50L288; Rakus et al, 2003) in which the N-terminal residues (1-50) were derived from the other isozyme.…”
Section: Discussionmentioning
confidence: 97%
“…The liver FBPase is recognized as the regulatory enzyme of gluconeogenesis [53], and high FBPase level is regarded as a way to speed up the production of ATP in order to resist ROS. In our study, MP resulted in an increased expression of FBPase, and we propose that the overexpression of FBPase participated in relieving ROS induced by MP.…”
Section: Mp Induction Of Differentially Expressed Proteins Involved Imentioning
confidence: 99%
“…, the higher affinity (10–100 times lower I 0.5 , i.e. , the inhibitor concentration which causes 50% reduction of the enzyme catalysis) for AMP than either the liver or kidney enzymes [22][26]. Recent kinetic studies on mutant forms of human muscle and liver Fru-1,6-Pase indicated that Lys20 plays a pivotal role in the high affinity of human muscle Fru-1,6-Pase (hmFru-1,6-Pase) for AMP [25], [26].…”
Section: Introductionmentioning
confidence: 99%
“…, the inhibitor concentration which causes 50% reduction of the enzyme catalysis) for AMP than either the liver or kidney enzymes [22][26]. Recent kinetic studies on mutant forms of human muscle and liver Fru-1,6-Pase indicated that Lys20 plays a pivotal role in the high affinity of human muscle Fru-1,6-Pase (hmFru-1,6-Pase) for AMP [25], [26]. A comparison of the homology between Fru-1,6-pase from human muscle and human liver revealed that they share 77% sequence identity, and that muscle Fru-1,6-Pase must be encoded by a separate gene [23].…”
Section: Introductionmentioning
confidence: 99%